Acquisition of –Ing in English by Multilingual Adult Speakers in Germany and the US - Gulumser Efeoglu (Sakarya University Journal of Education)
The number of the multilingual speakers all over the world has been increasing steadily, which calls for closer analyses of multilingualism as a phenomenon. The current study aims at investigating multilingual speakers’ spoken and written English productions in formal and informal contexts within the boundaries of social context of migration. As for the purposes of the study, data coming from four groups in Germany and the US (32 participants and 24 speakers from RUEG corpus, 56 people in total) via data collection tools such as Language Situations (Wiese 2018), Linguistic Background Questionnaire and c-tests were analyzed both qualitatively and quantitatively. The results were divergent. The comparison of -ing use only revealed that the acquisition of the progressive marker in L3? English differs in Germany and the US while -ing use in total Communication Units (henceforth CU) ratio signaled some cross-linguistic effects. However, there was no difference in within group comparisons obscuring multilingual-monolingual dichotomy within both Germany and the US. Also, task modality and registers were found to have a prominent effect on L3 patterns of English progressive morpheme -ing.